2013
DOI: 10.1088/0004-637x/770/2/145
|View full text |Cite
|
Sign up to set email alerts
|

Vlbi Astrometry of PSR J2222-0137: A Pulsar Distance Measured to 0.4% Accuracy

Abstract: The binary pulsar J2222−0137 is an enigmatic system containing a partially recycled millisecond pulsar and a companion of unknown nature. While the low eccentricity of the system favors a white dwarf companion, an unusual double neutron star system is also a possibility, and optical observations will be able to distinguish between these possibilities. In order to allow the absolute luminosity (or upper limit) of the companion object to be properly calibrated, we undertook astrometric observations with the Very… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
72
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(76 citation statements)
references
References 31 publications
4
72
0
Order By: Relevance
“…For both PSR J1022+1001 and PSR J2145-0750, a short observation (duration ∼15 minutes) was made in 2011 May to identify nearby compact radio sources that could be used as in-beam phase calibrators. The observation setup was identical to that described for the calibrator identification program in Deller et al (2013), with several short scans on pointing centers distributed around the target pulsar. From each pointing, ∼25 correlated data sets were produced centered on known radio sources located within the VLBA primary beam, using the multi-field capability of the DiFX software correlator (Deller et al 2011b).…”
Section: Vlbi Observationsmentioning
confidence: 99%
See 2 more Smart Citations
“…For both PSR J1022+1001 and PSR J2145-0750, a short observation (duration ∼15 minutes) was made in 2011 May to identify nearby compact radio sources that could be used as in-beam phase calibrators. The observation setup was identical to that described for the calibrator identification program in Deller et al (2013), with several short scans on pointing centers distributed around the target pulsar. From each pointing, ∼25 correlated data sets were produced centered on known radio sources located within the VLBA primary beam, using the multi-field capability of the DiFX software correlator (Deller et al 2011b).…”
Section: Vlbi Observationsmentioning
confidence: 99%
“…The data reduction used was very similar to that presented in Deller et al (2013) and will be described in detail in a forthcoming p PSR catalog paper (A. T. Deller et al 2016, in preparation); we summarize it briefly here. We made use of the ParselTongue (Kettenis et al 2006) Python interface to the AIPS package (Greisen 2003, p. 109).…”
Section: Vlbi Data Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…Another interesting target is the binary pulsar PSR J2222-0137, which contains a millisecond pulsar orbited by a companion of unknown nature (Deller et al 2013). As the system is seen nearly edge-on (sin i = 0.9985 ± 0.0005) and its orbital parameters are known, it is possible to observe it in search for the companion-induced signal around the transit time of the companion between the pulsar and Earth, or even to search for this signal in existing data.…”
Section: Observational Testsmentioning
confidence: 99%
“…For the systematic errors, so far, there have been two main ionospheric calibration strategies for L-band continuum astrometry: measure and remove the dispersive component of the ionospheric delays by using wide-spread bands to detect its frequency-dependent curva-ture (Brisken et al 2000(Brisken et al , 2002; or use in-beam astrometry to almost completely remove dynamic (random) and mitigate static (systematic) error terms (Chatterjee et al 2001(Chatterjee et al , 2009). Deller et al (2013Deller et al ( , 2016 demonstrated that by using in-beam calibrators with careful scheduling and data reduction, it is possible to measure parallaxes at a ∼10 µas-level precision despite the low frequency.…”
Section: Introductionmentioning
confidence: 99%